2018
DOI: 10.1111/bjd.16572
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival of secukinumab for moderate-to-severe plaque psoriasis

Abstract: Linked Article: Egeberg et al. Br J Dermatol 2018; 178:509–19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…Longer‐term, real‐world clinical data on secukinumab's survival based on patient profiles are presented. Our results show higher survival rates compared to those found in clinical trials . Previous studies have shown different survival rates .…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…Longer‐term, real‐world clinical data on secukinumab's survival based on patient profiles are presented. Our results show higher survival rates compared to those found in clinical trials . Previous studies have shown different survival rates .…”
Section: Resultscontrasting
confidence: 69%
“…On the other hand, Lee found that only 41.70% ( n = 48) of patients receiving secukinumab in their series did not require combined treatment or a change to their alternative therapy, therefore establishing the lowest survival rate published to date. Lee attributes the highest dropout rate to a longer follow‐up period in their series . Georgakopoulos et al .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the availability of various biologics, physicians observe a disturbingly high burden of non-response or loss of response. [13][14][15][16][45][46][47][48] As the introduction of biologics has shifted the golden standard from PASI75 to PASI90 and even PASI100, 49 it is possible to treat patients ambitiously and manage the disease in such a way that proper responses are maintained during treatment. Strict follow-up of clinical response as postulated in treat-to-target can enhance effective use of these expensive drugs in patients with moderateto-severe psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…The result, a multidimensional target consisting of both physician‐reported outcome and PRO, reflects the reality and complexity of psoriasis and therefore guides treatment decisions with sufficient patient involvement. Despite the availability of various biologics, physicians observe a disturbingly high burden of non‐response or loss of response . As the introduction of biologics has shifted the golden standard from PASI75 to PASI90 and even PASI100, it is possible to treat patients ambitiously and manage the disease in such a way that proper responses are maintained during treatment.…”
Section: Discussionmentioning
confidence: 99%